(untitled) (JOURNAL OF ADVANCES IN CHEMISTRY, 2016)
Studies on pH control in process engineering have shown a dramatic increase in the last decades. pH control systems were developed and used successfully on various applications of pH process plants in many industries especially in chemical processes, biotechnological industries, wastewater treatment and pharmaceuticals. The pH process is considered as a benchmark problem. Thus the research is ongoing on identification and control in pH process. In this paper, the mathematical model has been developed for a chemical process (pH process) and the conventional controllers such as PI and PID, Tyreus-Luyben has been designed and implemented. A control strategy based on tuning of a PID controller with Internal model controller (IMC), Direct synthesis method has been designed and implemented in the pH process. The experimental and simulation results obtained by various control algorithms are discussed.